O conflito entre a ética da alteridade de Emmanuel Levinas e o paradoxo da tolerância de Karl Popper : a dignidade da pessoa humana como garantia do pacto civilizatório - Farias, Júlio César Lima de (2024)
From the rubble of the events of the Second World War, the philosopher Emmanuel Levinas developed the idea of the "ethics of alterity", defending intersubjective living in difference, to enable the free expression of pluralism as an axiological paradigm. However, the applicability of this concept comes up against the "paradox of tolerance", presented by Karl Popper, which imposes a limit on the understanding of this pluralism as a value, resulting from the practice of Levinas' ethics. In this way, this work sought to reconcile Levinas' ethics of alterity with Popper's paradox of tolerance. It sought to answer the following question: how can we resolve the conflict between the consequences of the ethics of alterity and the warnings of the paradox of tolerance, without undermining the ethical-political importance of a plural society? One solution would be to find a foundation where, by agreeing that it is a basic value, the various manifestations of difference are possible. This fundamental value must avoid subjectivism and cultural impositions. We investigated whether the dignity of the human person is such a value. The dignity of the human person is the idea-synthesis of civilizational development, functioning as a principle of minimal guarantees recognized for all human beings. Thus, the application of the ethics of alterity finds its limits in this ethical-legal-political principle. Any manifestation of diversity must take place with this as its starting point. If it is not observed, the paradox of tolerance comes into play to repress existing abuses.